Symmetry Properties of Higher-Order Bernoulli Polynomials - Taekyun Kim; Kyung-Won Hwang; Young-Hee Kim (Advances in Difference Equations, 2009)
We investigate properties of identities and some interesting identities of symmetry for the Bernoulli polynomials of higher order using the multivariate p-adic invariant integral on ℤp.